Museums, heritage and indigenous voice : decolonising engagement - Onciul, Bryony (New York ; London : Routledge, 2015)
'Current discourse on Indigenous engagement in museum studies is often dominated by curatorial and academic perspectives, in which community voice, viewpoints, and reflections on their collaborations can be under-represented. This book provides a unique look at Indigenous perspectives on museum community engagement and the process of self-representation, specifically how the First Nations Elders of the Blackfoot Confederacy have worked with museums and heritage sites in Alberta, Canada, to represent their own culture and history. Situated in a post-colonial context, the case-study sites are places of contention, a politicized environment that highlights commonly hidden issues and naturalized inequalities built into current approaches to community engagement. Data from participant observation, archives, and in-depth interviewing with participants brings Blackfoot community voice into the text and provides an alternative understanding of self and cross-cultural representation. Focusing on the experiences of museum professionals and Blackfoot Elders who have worked with a number of museums and heritage sites, Indigenous Voices in Cultural Institutions unpicks the power and politics of engagement on a micro level and how it can be applied more broadly, by exposing the limits and challenges of cross-cultural engagement and community self-representation. The result is a volume that provides readers with an in-depth understanding of the nuances of self-representation and decolonization'--
Keywords: Museums -- Social aspects -- Canada; Museums and Indians -- Canada; Museums -- Political aspects -- Canada; Ethnological museums and collections -- Canada; Cultural property -- Canada; Museum exhibits -- Canada; ART / Collections, Catalogs, Exhibitions / General; ART / Museum Studies; ART / Native American; Canada -- Cultural policy